Protocol for the study and treatment of primary immune thrombocytopenia: ITP-2018 - Emilio Monteagudo; Itziar Astigarraga; Áurea Cervera; María Angeles Dasí; Ana Sastre; Rubén Berrueco; José Luis Dapena (Elsevier, 2019)
Primary immune thrombocytopenia, formerly known as immune thrombocytopenic purpura, is a disease for which the clinical and therapeutic management has always been controversial. The ITP working group of the Spanish Society of Paediatric Haematology and Oncology has updated its guidelines for diagnosis and treatment of primary immune thrombocytopenia in children, based on current guidelines, bibliographic review, clinical assays, and member consensus. The main objective is to reduce clinical variability in diagnostic and therapeutic procedures, in order to obtain best clinical results with minimal adverse events and good quality of life. Resumen: La trombocitopenia inmune primaria, anteriormente conocida como púrpura trombocitopénica inmune, es una enfermedad cuyo manejo diagnóstico y terapéutico ha sido siempre controvertido. La Sociedad Española de Hematología y Oncología Pediátricas, a través del grupo de trabajo de la PTI, ha actualizado el documento con las recomendaciones protocolizadas para el diagnóstico y tratamiento de esta enfermedad, basándose en las guías clínicas disponibles actualmente, revisiones bibliográficas, ensayos clínicos y el consenso de sus miembros. El objetivo principal es disminuir la variabilidad clínica en los procedimientos diagnósticos y terapéuticos con el fin de obtener los mejores resultados clínicos, los mínimos efectos adversos y preservar la calidad de vida.